Islamisasi Banyumas: Studi Historis Berdasarkan Babad Banyumas - Ischak Suryo Nugroho; Riris Eka Setiani; Dimas Indianto S.,; Wulandari Retnaningrum (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This study aims to examine Islamization in Banyumas based on the Babad Banyumas manuscript. This study traces the process of Islam entering Banyumas which began with the strong influence of the Demak Kingdom as the center of political power and the spread of Islam in Java. The role of important figures such as Ki Dipati Wargautama and the Sultan of Demak were identified as key in introducing Islamic teachings to the Banyumas community. The Babad Banyumas manuscript describes the gradual acceptance of Islam by the community, although it was marked by challenges from previously dominant traditional beliefs. This study aims to reveal how the Islamization process took place in Banyumas as narrated in the Babad Banyumas, identify key figures who played a role in the spread of Islam, and analyze the dynamics of interaction between Islam and traditional beliefs at that time. This study uses a qualitative method with a hermeneutic approach. Through text study, the Babad Banyumas manuscript is analyzed as a primary source to reveal the narrative of the Islamization process in Banyumas. The analysis includes the structure, context, and content of the text to understand the meaning and message contained. Literature studies from secondary sources such as books, journals, and related research are used to strengthen the data. The results of the study show that Islamization in Banyumas is a dynamic process, full of challenges, but takes place with a peaceful approach that prioritizes social harmony.Keywords: Islamization, Babad Banyumas, Islamic preaching.